2016
DOI: 10.5194/cp-2016-34
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Late Pleistocene to Holocene climate and limnological changes at Lake Karakul (Pamir Mountains, Tajikistan)

Abstract: Abstract. Lake Karakul, located in the eastern Pamir Mountains, Tajikistan, is today dominated by the Westerlies. It is a matter of debate whether the Indian Monsoon influenced the region in the past. We analysed an 11.25 m sediment core covering the last 29,000 years to assess and separate lake-internal and lake-external processes, and to infer changes in the predominant atmospheric circulation. Among the parameters indicating lake-external processes, high values in grain-size end-member (EM) 3 (wide grain-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 101 publications
(152 reference statements)
0
12
0
Order By: Relevance
“…Lake status is an index of the water balance (precipitation minus evaporation) over the lake and its catchment. Lake histories produced since the publication of the GLSDB have also been compiled and are included in our analyses—see the supporting information for details [ Bird et al ., ; Boomer et al ., ; Chen et al ., ; Chawchai et al ., ; Chen et al ., ; Ferronskii et al ., ; Fowell et al ., ; Gasse et al ., ; Grunert et al ., ; Kong et al ., ; Heinecke et al ., ; Herzschuh et al ., ; Hodell et al ., ; Huang et al ., , ; Jiang et al ., ; Jiang and Liu , ; Li and Morrill , ; Li et al ., , , ; Long et al ., ; Madsen et al ., ; Mathis et al ., ; Mingram et al ., ; Morinaga et al ., ; Morrill et al ., ; Pan et al ., ; Peck et al ., ; Penny et al ., ; Prokopenko et al ., ; Rades et al ., ; Ricketts et al ., ; Schwanghart et al ., ; Shen et al ., ; Sheng et al ., ; Wang et al ., ; Wang and Ji , ; Wünnemann et al ., , ; Xiao et al ., ; Yang et al ., ; Zhang et al ., , ; Zhao et al ., , , ; Zhou et al ., ]. BIOME 6000 provides pollen‐based reconstructions of vegetation for the MH [ Prentice et al ., ; Bigelow et al ., ], and the reconstructions for Eurasia have been updated by Binney et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Lake status is an index of the water balance (precipitation minus evaporation) over the lake and its catchment. Lake histories produced since the publication of the GLSDB have also been compiled and are included in our analyses—see the supporting information for details [ Bird et al ., ; Boomer et al ., ; Chen et al ., ; Chawchai et al ., ; Chen et al ., ; Ferronskii et al ., ; Fowell et al ., ; Gasse et al ., ; Grunert et al ., ; Kong et al ., ; Heinecke et al ., ; Herzschuh et al ., ; Hodell et al ., ; Huang et al ., , ; Jiang et al ., ; Jiang and Liu , ; Li and Morrill , ; Li et al ., , , ; Long et al ., ; Madsen et al ., ; Mathis et al ., ; Mingram et al ., ; Morinaga et al ., ; Morrill et al ., ; Pan et al ., ; Peck et al ., ; Penny et al ., ; Prokopenko et al ., ; Rades et al ., ; Ricketts et al ., ; Schwanghart et al ., ; Shen et al ., ; Sheng et al ., ; Wang et al ., ; Wang and Ji , ; Wünnemann et al ., , ; Xiao et al ., ; Yang et al ., ; Zhang et al ., , ; Zhao et al ., , , ; Zhou et al ., ]. BIOME 6000 provides pollen‐based reconstructions of vegetation for the MH [ Prentice et al ., ; Bigelow et al ., ], and the reconstructions for Eurasia have been updated by Binney et al .…”
Section: Methodsmentioning
confidence: 97%
“…Lake status is an index of the water balance (precipitation minus evaporation) over the lake and its catchment. Lake histories produced since the publication of the GLSDB have also been compiled and are included in our analyses-see the supporting information for details [Bird et al, 2014;Boomer et al, 2000;Chen et al, 2008;Chawchai et al, 2013;Chen et al, 2003;Ferronskii et al, 2003;Fowell et al, 2003;Gasse et al, 1996;Grunert et al, 2000;Kong et al, 2007;Heinecke et al, 2016;Herzschuh et al, 2004;Hodell et al, 1999;Huang et al, 2009Huang et al, , 2014Li and Morrill, 2010;Li et al, 2011Li et al, , 2014aLi et al, , 2014bLong et al, 2012;Madsen et al, 2008;Mathis et al, 2012;Mingram et al, 2004;Morinaga et al, 1993;Morrill et al, 2006;Pan et al, 2012;Peck et al, 2002;Penny et al, 1996;Prokopenko et al, 2007;Rades et al, 2015;Ricketts et al, 2001;Schwanghart et al, 2008;Shen et al, 2005;Sheng et al, 2017;Wang et al, 2017;Wang and Ji, 1995;Wünnemann et al, 2003Wünnemann et al, , 2006Xiao et al, 2008;Yang et ...…”
Section: Methodsmentioning
confidence: 99%
“…At the lake Issyk Kul in Kyrghystan, Ricketts et al (2001) identified a change in the climatic condition of the basin around 6900 BP (transition from a fresh-water open-basin, well-mixed system to a closed-basin, more saline and relatively poorly mixed system) related to increasing aridity and atmospheric changes, diagnosed as the strengthening of the Siberian High, or the weakening of the Southwest Asian Low (Indian monsoon). The development of the Lake Karakul in Tajikistan marked by a reduction of the lake levels from 6600 BP suggests a similar aridification of the climate (Heinecke et al 2016). Later, from 4200 to 3500 BP, a high water level resulting from an intake from the melting of glaciers, snow fields and frozen grounds indicates warm climatic conditions, whereas subsequently (3500-1600 BP), a rapid cooling and a lower water level has been reconstructed (Mischke et al 2010).…”
Section: The Palaeoclimate Datamentioning
confidence: 99%
“…As one of the driest areas in the world, southern Central Asia is undergoing the influence of different climatic systems at different space and time scales, but presently dominated by prevailing winds from the West, so-called 'westerlies' (Cheng et al 2012(Cheng et al , 2016Heinecke et al 2016;Lauterbach et al 2014;Wang et al 2010). It belongs to the desert climatic zones, with a semi-arid to arid climate, characterized by low rainfall from the end of fall to mid spring and by a maximum exposure to the sun and high temperatures the rest of the year (Mannig et al 2013).…”
Section: Short Note On the Geography Of Southern Central Asia And Normentioning
confidence: 99%
See 1 more Smart Citation